BODY MEASUREMENT IN GARMENT CONSTRUCTION - Mamatqulova Qunduzxan Umarovna (Journals Park Publishing, 2024)
This article provides information on what garment construction is and how to take body measurements
Keywords: materials, structure, installation methods, polyester, cotton, stick, handle.